Hier sind wir! Junge feministische Sozialpädagoginnen und ihre Aufforderung zu einem Dialog der Generationen - Kagerbauer, Linda (Büchner-Verlag, 2008)
Here we are! A title that whets the appetite for the perspective of a young feminist, that also wants to invite joint dialogues and provides insights into the historical development of a feminist professional understanding within the framework of the first and second German women's movements. In addition, the focus is on a new generation of feminist women and professional self-understandings are explored. Taking political developments into account, current references and historically developed women's movement traditions are thus critically examined and alternatives are developed with regard to intergenerational relationships.